What can We Learn from Biological Systems when Applying the Law of System Completeness?. (2015) - Cohen, Yael Helfman; Reich, Yoram; Greenberg, Sara
Abstract: Biological systems have been evolving for millions of years while technical systems have been evolving for only a few hundred years. Are biological systems architectures and functions similar to those found in technical systems or are they different systems altogether? Biological Systems were analyzed in terms of the Law of System Completeness: engine, transmission unit, working unit and control pattern structures plus sources and forms of energy transmitted. The analysis shows several interesting insights in terms of sustainability aspects such as: (1) Biological systems use external energy sources almost without any extra cost by adopting ready available environmental resources. (2) In biological systems, essential elements, such as the working unit or the control unit, may be provided by elements and components from their surrounding environment. (3) Analysis of biological systems using the law of system completeness provides an operational language that eases the description of those systems and improves their understanding. The examples provided in this study contribute to a better understanding of biological systems and can be further used as guidelines to drive innovative designs of sustainable technical systems.